Parental employment at the onset of the pandemic: Effects of lockdowns and government policies - Kabir Dasgupta; Linda Kirkpatrick; Alexander Plum (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2024)
The COVID-19 pandemic had disproportionate impacts on women's employment, especially for mothers with school-age and younger children. However, the impacts likely varied depending on the type of policy response adopted by various governments. New Zealand presents a unique policy setting in which one of the strictest lockdown restrictions was combined with a generous wage subsidy scheme to secure employment. We utilize tax records to compare employment patterns of parents from the pandemic period (treatment group) to similar parents from a recent pre-pandemic period (control group). For mothers whose youngest child is aged between one and 12, we find a 1-2-percentage point decline in the likelihood of being employed in the first six months of the pandemic; for fathers, we hardly see any significant changes in employment. Additionally, the decline in mothers' employment rates is mainly driven by those not employed in the month before the lockdown. We also find similar employment patterns for future parents who had no children during the evaluation period. This indicates that the adverse labour market impacts are not uniquely experienced by mothers, but by women in general.
Keywords: D10; D13; E24; 330; Pandemic; Employment; Parental gap; Administrative data